1972
DOI: 10.1128/aac.1.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Tilorone Hydrochloride: Lack of Correlation Between Interferon Induction and Viral Protection

Abstract: The protection of mice against MM virus infection and the induction of circulating interferon by tilorone hydrochloride were determined. Whereas protection was evident with doses of 0.15 and 1.5 mg/kg, interferon was not detected with doses lower than 150 mg/kg. Protection was apparently not dependent on interferon induction.Tilorone hydrochloride, the orange, watersoluble dihydrochloride salt of 2,7-bis[2-(diethylamino) ethoxy] fluoren-9-one, is a broadspectrum antiviral agent (5). In mice, it is effective ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…These findings suggest that the amount of IFN in the lung has an important role in the defense against influenza virus infection in mice. Similar results showing that the amounts of IFN in virus propagating tissues, but not in circulating IFN titers correlate to the resistance to viral diseases have been reported with pyran and poly I:C on mengovirus infected mice (Merigan et al 1970) and with tilorone hydrochloride on MM virus infected mice (Giron et al 1972).…”
Section: Discussionsupporting
confidence: 71%
“…These findings suggest that the amount of IFN in the lung has an important role in the defense against influenza virus infection in mice. Similar results showing that the amounts of IFN in virus propagating tissues, but not in circulating IFN titers correlate to the resistance to viral diseases have been reported with pyran and poly I:C on mengovirus infected mice (Merigan et al 1970) and with tilorone hydrochloride on MM virus infected mice (Giron et al 1972).…”
Section: Discussionsupporting
confidence: 71%
“…2). However, the presence of tilorone (10 ug/ml) did not affect significantly the rate of adsorption of the two virus preparations tested (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Tilorone hydrochloride at a concentration of 10 ,ug/ml very efficiently inhibited herpes simplex virus growth in BSC1 cells when the virus is infected at a low multiplicity of infection. The adsorption of the virus was not affected by the drug, and the penetration of the deoxyribonucleic acid of the input virus into the cytoplasm and nuclei proceeded normally when tilorone hydrochloride was present.…”
mentioning
confidence: 99%
“…Giron et al (3) reported that protection of mice with tilorone hydrochloride against MM virus is apparently not dependent on interferon induction. In their studies, circulating interferon was not detected with i.p.…”
mentioning
confidence: 99%
“…Giron et al (3) concluded that determination of circulating interferon concentration is of limited value in assessing antiviral activity, since protection can be demonstrated without the simultaneous detection of interferon. In contrast, others report that protection of mice against intranasal infection with VSV is directly related to the concentrations of interferon induced by different doses of tilorone (1).…”
mentioning
confidence: 99%